2003
DOI: 10.2176/nmc.43.100
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Abscess Showing High Uptake of Thallium-201 on Single Photon Emission Computed Tomography. Case Report.

Abstract: A 32-year-old female presented with a rare case of pituitary abscess manifesting as homonymous hemianopsia. Serum prolactin level was slightly high (40.8 ng/ml). Magnetic resonance (MR) imaging showed the content of the lesion as homogeneously isointense on the T 1 -weighted images and hyperintense on the T 2 -weighted images. The capsule of the lesion, which appeared thin and smooth, was enhanced by gadolinium. Dural enhancement around the sella turcica was also recognized. Thallium-201 single photon emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
3
4
0
Order By: Relevance
“…The second point is the "perfusion" pattern observed in the ictal SPECT. Similar PET or SPECT findings with different radiotracers have been observed in pharyngeal and pituitary neuroendocrine tumors or abscess (4,5) . Our clinical and laboratory investigations excluded the presence of mass lesions.…”
Section: Discussionsupporting
confidence: 67%
“…The second point is the "perfusion" pattern observed in the ictal SPECT. Similar PET or SPECT findings with different radiotracers have been observed in pharyngeal and pituitary neuroendocrine tumors or abscess (4,5) . Our clinical and laboratory investigations excluded the presence of mass lesions.…”
Section: Discussionsupporting
confidence: 67%
“…Shimamura et al suggests that a way of differentiating both pituitary lesions is by the high uptake of the abscess on thallium-210 single-photon emission CT on the early and delayed images. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Vates et al reported 24 cases drawn from a series of more than 3500 patients who underwent pituitary surgery [2]. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], and a summary of these cases, which we selected for analysis, has been tabulated in Table 2, 3 and 4.…”
Section: Discussionmentioning
confidence: 99%